Life Cycle CO2 Assessment by Block Type Changes of Apartment Housing - Cheonghoon Baek (Sustainability, 2016)
The block type and structural systems in buildings affect the amount of building materials required as well as the CO2 emissions that occur throughout the building life cycle (LCCO2). The purpose of this study was to assess the life cycle CO2 emissions when an apartment housing with ‘flat-type’ blocks (the reference case) was replaced with more sustainable ‘T-type’ blocks with fewer CO2 emissions (the alternative case) maintaining the same total floor area. The quantity of building materials used and building energy simulations were analyzed for each block type using building information modeling techniques, and improvements in LCCO2 emission were calculated by considering high-strength concrete alternatives. By changing the bearing wall system of the ‘flat-type’ block to the ‘column and beam’ system of the ‘T-type’ block, LCCO2 emissions of the alternative case were 4299 kg-CO2/m2, of which 26% was at the construction stage, 73% was as the operational stage and 1% was at the dismantling and disposal stage. These total LCCO2 emissions were 30% less than the reference case.